Identification of an eight-LncRNA signature as the prognostic LncRNA markers in hepatocellular carcinoma patients - Li, Sixu; Zeng, Weiping; Wang, Dongfang; Tan, Keai Sinn; Tan, Wen; Gu, Li (Penerbit Universiti Kebangsaan Malaysia, 2022)
Long non-coding RNA (lncRNA) signature has been reputable for the predetermination of cancer prognosis. In the present study, we constructed a lncRNA model to predict the survival outcomes for hepatocellular carcinoma (HCC) patients. Using the transcriptome data from TCGA HCC samples, we identified that NEAT1 and MALAT1 were highly expressed in HCC and other tumor subtypes compared to the adjacent normal tissues. Based on the LASSO Cox regression model, we identified an eight-lncRNA signature that significantly correlated with the overall survival and disease-free survival of the HCC training group. The prognostic value of this signature was validated using the test group. Further analysis suggested that this signature was associated with the clinicopathological parameters such as vascular tumor invasion, pathological stage, and tumor grade. Integrated functional analysis showed that these eight-lncRNAs were involved in the cell cycle, metabolic process, and immune response. In conclusion, we constructed an applicable eight-lncRNA signature that is robust and reliable for the prognosis of HCC. This signature may provide an efficient clinical prediction for HCC patients, and further study is required to uncover the function of the identified lncRNAs better.